Comprehensive Study of Cobalt doped TiO2 Thin Films for Photo Catalytic Applications - Singh, Davinder (European Journal of Applied Sciences, 2023)
In this study, Pure and Cobalt (Co) doped titanium dioxide (TiO2) thin films on glass substrate were prepared by using sol-gel dip coating process. The effects of Co doping on the structural, optical and photo catalytic properties of TiO2 thin films were investigated. The as-prepared films were annealed at temperature 500°C for 1h and characterized by X-ray diffraction (XRD), atomic force microscopy (AFM), photoluminescence (PL) and UV-Visible spectroscopic studies. The XRD patterns and AFM images revealed a polycrystalline structure for all samples. PL spectra shows that charge separation increased upto 0.5 mol% Co doped TiO2 thin films. Optical band gap, refractive index, optical conductivity and extinction coefficients of these films were determined using transmittance spectra. Band gap energy of the Co doped anatase TiO2 films is found to decrease with increasing Co concentration. The refractive index was found to increase from 2.12 to 2.33 with increase in Co concentration from 0 to 1.0-mol %. The optimal Cobalt doping concentration is 0.5 mol% for better photo catalytic activity as supported by Photoluminescence spectra.